Quantitative SWOT analysis for prioritizing ecotourism-planning decisions in protected areas: Igneada case - Demir, Sara; Esbah, Hayriye; Akgun, Aliye Ahu (Informa UK Limited, 2016)
ABSTRACTAs environmental problems and pressures on natural resources escalate, awareness building and efforts to protect natural areas have also became a major goal to ensure sustainability. Ecotourism is one of the major activities to protect natural and cultural resources, while also providing economic benefits to both local people and government. Successful ecotourism planning is a function of establishing sound goals and criteria. In this paper, we have presented the example of Igneada, Turkey, as a case to elaborate this point. Igneada a coastal town, located on the north-west Black Sea region of Turkey, was declared a national park in 2007. The park is well known for its longos forests (flooded), lagoons, endemic and endangered species, and wildlife. However, currently, unsustainable economic activities, overgrazing, and urbanization cause threats to its sensitive ecosystems. Promoting ecotourism is a sustainable approach to balance economic, social, and environmental aspects in the development of I...